2005
DOI: 10.1007/s00421-005-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in muscle activation and leg extension performance after different running exercises in elite long distance runners

Abstract: This study investigated acute changes in muscle activation and muscular power performance after three different running exercises in elite long-distance runners. Twenty-two nationally and internationally ranked long-distance runners performed first an incremental treadmill running test until exhaustion (MR) and then 40 min continuous (TR) and intermittent (2 min run/2 min rest) (IR) running exercises at an intensity of 80 and 100% of the velocity associated with VO(2max), respectively. Muscle activation and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 49 publications
6
59
0
2
Order By: Relevance
“…Changes in SSC performance following prolonged exercise have been associated with corresponding reductions in muscle activity (Avela & Komi, 1998;Paavolainen et al, 1999;Vuorimaa et al, 2006). Vuorimaa and colleagues (2006) reported reductions in the electromyographic (EMG) activity of lower limb muscles during a countermovement jump completed after 40 min of continuous or intermittent running.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Changes in SSC performance following prolonged exercise have been associated with corresponding reductions in muscle activity (Avela & Komi, 1998;Paavolainen et al, 1999;Vuorimaa et al, 2006). Vuorimaa and colleagues (2006) reported reductions in the electromyographic (EMG) activity of lower limb muscles during a countermovement jump completed after 40 min of continuous or intermittent running.…”
Section: Introductionmentioning
confidence: 97%
“…Decrements in SSC performance are relatively simple to monitor, with differences in squat and countermovement jump performance highlighting pre-stretch augmentation (Byrne & Eston, 2002;Kubo, Kawakami, & Fukunaga, 1999). When comparing concentric-only squat jumps with countermovement jumps, previous research has shown that acute fatigue is attenuated during SSC jumps (Byrne & Eston, 2002), acute fatigue leads to greater decrements in SSC jumps (Horita, Komi, Hamalainen, & Avela, 2003), and that prolonged exercise can improve SSC jump performance (Vuorimaa, Virlander, Kurkilahti, Vasankari, & Hakkinen, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…EMG has been widely used during running studies (Kyröläinen et al, 2005;Komi, 1986, 1987;Sloniger et al, 1997;Vuorimaa et al, 2006), and has contributed to the understanding of the running gait and neuromuscular causes of fatigue during running activity. Furthermore it is known that EMG amplitude of leg muscles increases with increased running speed (Dietz et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Tem sido demonstrado que músculos monoarticulares desempenham importante papel na produção de movimento na articulação do joelho, enquanto que músculos biarticulares, como o BF, parecem fornecer ajustes refinados no controle da distribuição dos torques produzidos nestas articulações 20,21 . Obviamente, também é possível que as diferenças específicas no BF sejam consequência de características individuais dos sujeitos avaliados neste estudo 22 .…”
Section: Resultsunclassified